PELATIHAN RISET PASAR DENGAN GOOGLE FORM UNTUK MEMBANGUN MEREK DIGITAL PADA PERAN KOMUNITAS UMKM KLUBANOSTIC DI KABUPATEN BREBES - agnes dwita susilawati agnes_dwita; Setyowati Subroto; Mei Rani Amalia; Ira Maya Hapsari; Abdulloh Mubarok; Baihaqi Fanani; Adilah Permananingrum; Niken Wahyu; Dien Noviany Rahmatika; Dewi Indriasih; Eva Anggra Yunita (Universitas Majalengka, 2022)
Business competition is very fierce, especially where everything almost happens online, thus increasing competition to the global stage. This fierce competition is one of the reasons why in running any business, including MSMEs (Micro, Small and Medium Enterprises) digitalization is needed. The number of MSMEs in Indonesia experiences an increasing trend every year, according to data from BPS The number of MSMEs in Indonesia in 2019 has increased by 1.98% with the magnitude of the increase making competition between MSMEs already very large. This makes MSMEs must always innovate to create products that are acceptable to the market. The rapid development of internet technology, especially in Indonesia, has largely changed the pattern of people's lives from various sides. Based on survey data from the Indonesian Internet Service Providers Association (APJII) in 2020, the number of internet users in Indonesia reached 171.1 million, this number has increased in 2021 by 202.7 million (based on the Communication and Information Technology report) and this number will continue to increase significantly. The Brebes MSME Clubanostic is an MSME community that has been incorporated and is located in Brebes Regency. Established since November 11, 2018, which started from KLUBAN (Banjaratna MSME Family) Banjaratna is a village from Bulakamba Brebes District. From the description above, the MSMEs of the Klubanostic Community of Brebes Regency in collaboration with the Faculty of Economics and Business UPS Tegal are very interested in holding a community service program, namely appropriate training in activities to start or develop existing citizen businesses.